Trade Cooperation The Purpose, Design and Effects of Preferential Trade Agreements - Dür, Andreas 1976- (Cambridge University Press, 2015)
This unique collection of original essays describes preferential trade agreements, explains why they have spread and explores their effects
Description based on publisher supplied metadata and other sources
Keywords: Favored nation clause; Reciprocity (Commerce); Präferenzsystem; Handelsabkommen; Aufsatzsammlung